Methane production in grazing cattle supplemented with silage, concentrate and tannins in the Peruvian highlands during the dry season - Moscoso M., Juan E. (2017)
The aim of the study was to determine the methane production in cattle grazing in the Peruvian highlands in a pasture of Festuca dolichophylla - Muhlenbergia fastigiata (Chilliguar), supplemented with silage and concentrate or tannins during the dry season (August). The study was conducted at the Experimental Centre «La Raya», Cusco, Peru, located at an altitude of 4200 m. Three treatments were used (T1: natural grass + oat silage, T2: as in T1 + tannins, T3: as in T1 + concentrate). Each treatment had four replicates distributed in a hierarchical design. Methane determination was performed using the sulfur hexafluoride (SF6) marker technique. The measurement was during 24 h for 7 d. The average energy content in the pasture was 4.1 Mcal GE/g, organic matter 91.8%, crude protein 10.3% and dry matter 91.17%. The methane (g/d) production for T1 was 421.7 ± 43.4, for T2 was 330.6 ± 66.7 and for T3 was 367.7 ± 116.5. The use of tannins significantly reduced (p<0.05) methane emissions from only silage supplementation or silage plus concentrate.